Conservative management of Riga-Fede disease - Mishra, Pratibha; Dali, Mamta; Koirala, Bandana (Journal of Nepalese Association of Pediatric Dentistry, 2023)
of ventral surface of the tongue by teeth. This may occur very early in life due to the presence of precociously erupted teeth or later during infancy at about 6-8 months during the time of eruption of mandibular central incisors. This could be a manifestation of developmental anomaly or an underlying neurologic disorder, including both the incidental and syndrome-associated natal teeth and inherited sensory neuropathies (e.g. familial dysautonomia). Treatment should begin conservatively and aim on eliminating the source of trauma. As there was no risk for aspiration of the tooth in this case, a conservative treatment was chosen by grinding the incisal edge of the tooth and topical application of choline salicylate ointment leading to a satisfactory healing in 10 days.